2008
DOI: 10.1007/s00232-008-9126-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytosolic pH on Epithelial Na+ Channel in Normal and Cystic Fibrosis Sweat Ducts

Abstract: The activities of cystic fibrosis transmembrane conductance regulator (CFTR) Cl(-) channel and the amiloride-sensitive epithelial Na(+) channel (ENaC) are acutely coordinated in the sweat duct. However, the mechanisms responsible for cross-talk between these ion channels are unknown. Previous studies indicated that luminal pH of sweat ducts varies over 3 pH units and that the cytoplasmic pH affects both CFTR and ENaC. Therefore, using basolaterally alpha-toxin-permeabilized apical membrane preparations of swea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The lumennegative transepithelial potential is most likely generated by a combination of K ϩ channels expressed in the basolateral membrane and Na ϩ and Cl Ϫ channels expressed in the apical membrane (9,10,36). A possible cause for the reduced transepithelial potential in mice lacking pendrin is an inhibition of the apical Na ϩ channels or the basolateral K ϩ channels by an acidic cytosolic pH (47). Whether the more acidic pH in the follicular lumen is associated with a more acidic cytosolic pH, however, is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The lumennegative transepithelial potential is most likely generated by a combination of K ϩ channels expressed in the basolateral membrane and Na ϩ and Cl Ϫ channels expressed in the apical membrane (9,10,36). A possible cause for the reduced transepithelial potential in mice lacking pendrin is an inhibition of the apical Na ϩ channels or the basolateral K ϩ channels by an acidic cytosolic pH (47). Whether the more acidic pH in the follicular lumen is associated with a more acidic cytosolic pH, however, is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…39,[46][47][48] Also, the in vivo activity of ENaC, the lithium entry site of principal cells, has been reported to be functionally paired with CA activity, because CA inhibition by acetazolamide reduced the intracellular pH and ENaC activity in sweat duct cells and colon. 49,50 However, mpkCCD cells may not fully represent principal cells, and because intercalated cells express abundant levels of CA2, -4, 52,53 it has been suggested that acidosis-induced proliferation of a-intercalated cells may contribute to Li-NDI. 16 It is unlikely, however, that attenuation of Li-NDI in our mice is caused by direct action of acetazolamide on a-intercalated cells or collecting duct remodeling for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…An important next step would be to explore the effects of modeling the pH along the duct. We expect pH to have an effect on bicarbonate due to buffering, but pH may also affect the membrane potential and the sodium concentration through the ENaC channel (42).…”
Section: Discussionmentioning
confidence: 99%